In house solution - Mohamed Noah, Roha; Sa’aidon, Ammarhaziq; Shamsul Akmar, Muhammad Suhaimi; Azlie, Muhammad Syamel; Naushad, Imtiaaz (2022)
This study aims to identify students’ feedback on solving simultaneous equation problems using proposed calculator activity In-House Solutions. In-House Solutions was proposed as some students were having difficulties in solving equations problems with using the existing calculators equipped with various formula facilities. Two aspects have been focused on, namely the processes and strategies used by students to solve simultaneous equation problems using calculators effectively. The study involved 27 Pre-Diploma students from UiTM Johor. In 2017, Abbas, Benchohra, Lazreg & Zhou conducted a data collection focusing on activities before using the calculator and after using the calculator. The data obtained were analyzed quantitatively using linear scores proposed by Matar (2018). The problem- solving process in this study includes four phases namely understanding the problem, planning solutions, implementing planning and reviewing. The study also showed that students used various problem-solving processes and strategies when using the calculator activity effectively compared to without using the calculator activity. Integral equations play an important role in mathematical analysis of natural and learning problems. Due to this importance, researchers have been devising new and improved ways to find accurate and efficient solutions to integral equations for decades. This study recorded positive feedback from students who used In-House Solutions in solving the equation problems.